2009
DOI: 10.1159/000252771
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-4 Activation in Association with Decreased Adenosine Deaminase Activity May Be a Factor for Gastric Ulcer

Abstract: Background/Aims: Adenosine deaminase (ADA)-deficient disease, a severe combined immunodeficiency, is most commonly associated with gastrointestinal disorders such as ulcer. The present study investigated the role of ADA in the pathogenesis of gastric ulcer. Methods: ADA activity was measured in a variety of organs and tissues from rats and in human gastric biopsy samples from patients who underwent gastrofiberscope. An MTT assay and TUNEL staining were carried out, and activity of caspase-3 and -4 was enzymati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…1C). These findings confirm previously reported findings, suggesting that caspase-4 contributes to the inflammation and mucosal damage that occur during ulcer formation (15).…”
Section: Increased Caspase-4 Expression In Patient Ulcer Biopsiessupporting
confidence: 93%
See 1 more Smart Citation
“…1C). These findings confirm previously reported findings, suggesting that caspase-4 contributes to the inflammation and mucosal damage that occur during ulcer formation (15).…”
Section: Increased Caspase-4 Expression In Patient Ulcer Biopsiessupporting
confidence: 93%
“…In this study, we report that caspase-4 is induced in peptic ulcer tissue, suggesting that noncanonical inflammasome activation and pyroptosis are processes participating in ulcer formation. Caspase-4 has previously been linked to decreased adenosine deaminase activity and implicated as a factor inducing gastric ulcers (15). Immune cells, such as macrophages, contribute to peptic ulcer formation through bacterial-induced inflammation (16).…”
Section: Introductionmentioning
confidence: 99%
“…As for CASP4, this protein can be activated by declines in adenosine deaminase activity and could induce gastric epithelial cell apoptosis, promoting the formation of gastric ulcers; however, a small population of cells may undergo malignant transformation (32). The diagnostic value of adenosine deaminase is of less importance as its activity in GC did not significantly differ to that in normal mucosa (33).…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, low extracellular concentrations of adenosine have been reported to increase beta-cell insulin release and proliferation via adenosine receptor activation [39]. On the other hand, high intracellular adenosine concentrations are known to promote cell death in different cells with decreased capacity for adenosine disposal (ADA-deficiency), such as immune cells in ADA-severe combined immune deficiency, neuronal cells, endothelial cells, epithelial cells, and cancer cells [40][41][42][43][44][45]. We have observed that high adenosine levels are toxic to beta cells [33], suggesting that the inherent capacity of beta cells to handle buildup of intracellular adenosine is low.…”
Section: Discussionmentioning
confidence: 99%